Extension of fitness evaluations with muscle oxygen saturation measurements based on near-infrared spectroscopy analysis during cardiopulmonary exercise testing in elite athletes. (3rd October 2022) - Babity, M; Zamodics, M; Kovacs, E; Konig, A; Rakoczi, R; Horvath, M; Kiss, A; Herczeg, S Z; Varga, A; Fabian, A; Lakatos, B K; Vago, H; et al.
Abstract: Introduction: Many cardiovascular parameters of sport adaptation have become an area of detailed research in recent decades. However, details of local circulatory and metabolic processes ongoing in the working muscles during physical exercise need to be revealed. Purpose: Our aim was to extend cardiopulmonary exercise testing with near-infrared spectroscopy measurements to focus on observing local changes in the contracting muscles during running. Methods: Mixed muscle oxygen saturation values (SmO2) measured in the left vastus lateralis muscle of athletes were analyzed by near-infrared spectroscopy during vita maxima treadmill cardiopulmonary exercise testing with 2-min fingertip lactate measurements. Body composition analysis was carried out with bioimpedance method. One-way repeated measures ANOVA, Tukey post-hoc test, Shapiro–Wilk test and Pearson correlation were used for statistical analysis. Results: The results of 66 elite athletes (male: 40; age: 17.9±3.6 y; training: 17.7±6.6 h/w; water polo player: 56, wrestler: 8, basketball player: 2) were analyzed. The 10-second averaged values of the measured saturation values were examined at rest (65.8±11.1%), at the anaerobic threshold (40.7±22.8%), at maximum load (30.2±20.5%) and after 5 minutes of cool-down (70.9±12.8%). Significant differences were measured between the four measurement time points in all pairings. A negative correlation was found between the achieved maximal oxygen uptake and the muscle oxygen saturation values measured at the anaerobic threshold and at the maximal load (respectively r=−0.30, p<0.02; r=−0.32, p<0.01). Oxygen uptake at the end of cool-down was also negatively correlated with muscle oxygen saturation values measured at the anaerobic threshold and at the peak of exercise (respectively r=−0.27, p<0.05; r=−0.27, p<0.05). The fat-free mass of the identical limb showed negative correlation with the muscle oxygen saturation values measured at the anaerobic threshold, at the maximal load and at the cool-down (respectively r=−0.43, p<0.01; r=−0.44, p<0.01; r=−0.35, p<0.01), while positive interactions were observed between the body-fat mass of the same limb and the muscle oxygen saturation values (respectively r=0.51, p<0.01; r=0.55, p<0.01; r=0.41, p<0.01). Muscle oxygen saturation values showed no significant correlations with exercise time, lactate levels, or heart rate measurements. Conclusions: By our results, muscle oxygen saturation measurements can be reliably applied during exercise physiological measurements. During exercise, muscle oxygen saturation values negatively correlated with oxygen uptake. At the cool-down phase, a rebound effect could be observed compared to the resting measurements. On the identical limb, the higher the muscle mass was, the higher muscle desaturation could be measured. This easy-to-perform test provides insight into muscle metabolism processes and can help with training planning and athlete follow-up. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This project was supported by a grant from the National Research, Development and Innovation Office (NKFIH) of Hungary (K 135076). Supported by the ÚNKP-21-3-I-SE-68 New National Excellence Program of the Ministry for Innovation and Technology from the Source of the National Research, Development and Innovation fund.